Tourists want to be spooked, not schooled: sustaining indigenous tourism in the Bastimentos Island National Marine Park, Bocas del Toro, Panama. Issue 2 (3rd April 2021) - Mach, Leon; Vahradian, Dylan
ABSTRACT: This article explores the intersection between Indigenous peoples, protected areas, and tourism through focus group interviews with Ngöbe settlements in Bahía Honda, Bocas del Toro, Panama. The aim was to co-construct context-specific knowledge related to their experiences with the imposition of a protected area and subsequent efforts to establish sustainable Indigenous tourism. We find that lacking Indigenous tourism demand and competition over bat cave tourism have led to changes in land ethics, community fragmentation and conflict. Lacking coordinated management has also facilitated an increase in externally operated cave tours with social and environmental consequences. The latest protected area management plan calls for investment and monitoring in bat cave tourism without mentioning existing relations and tensions. Findings reaffirm the importance of secure land rights, gauging tourist demand before starting programs and creating collaborative and adaptive management strategies for operationalizing sustainable Indigenous tourism in and around protected areas.